Myelo-deception: Luspatercept & TGF-Beta ligand traps in myeloid diseases & anemia. (October 2020) - Feld, Jonathan; Navada, Shyamala C.; Silverman, Lewis R.
Highlights: MEDALIST trial led to Luspatercept FDA-approval, first drug approved for MDS since 2006. Novel mechanism of trapping TGF-Beta ligands, leading to erythroid maturation. Indicated for lower-risk MDS with ringed sideroblasts relapsed/refractory to ESA. COMMANDS phase III trial will compare luspatercept to ESA as first-line treatment. Abstract: Myelodysplastic syndromes (MDS) encompass a clinically heterogenous group of diseases defined by a clonal bone marrow failure state. Patients with lower-risk MDS primarily suffer from the consequences of anemia, with a subset having increased risks of bleeding and infection. There are few good therapeutic options for this patient population, as patients are dependent on cytokine support to improve hematopoiesis. Our review will discuss luspatercept, a transforming growth factor (TGF)-Beta ligand trap, the first new Food & Drug Administration (FDA)-approved treatment in MDS in over a decade. We will explore the different TGF-Beta ligand traps that have been developed for a number of diseases, with a focus on myeloid malignancies.